Childhood socioeconomic disadvantage as a determinant of late-life physical function in older Japanese people. (March 2020) - Murayama, Hiroshi; Sugiyama, Mika; Inagaki, Hiroki; Edahiro, Ayako; Okamura, Tsuyoshi; Ura, Chiaki; Miyamae, Fumiko; Motokawa, Keiko; Awata, Shuichi
Highlights: Lower childhood socioeconomic status was associated with lower physical function in older Japanese people. This association was stronger in women than in men. Policymakers should not ignore the long-term impact of childhood socioeconomic disadvantage on late-life physical function. An upstream approach should be considered to promote healthy aging. Abstract: Background: In this study, we examined the relationship between childhood socioeconomic status and physical function among older Japanese people, and investigated whether there is a sex variation in this association. Methods: We administered a cross-sectional questionnaire survey to all independent community-dwelling individuals ≥65 years old, living in Adachi Ward, Tokyo (N = 132, 005). Participants self-reported their physical function using the Motor Fitness Scale, and we divided the scores into quartiles for analysis. Childhood socioeconomic status was retrospectively assessed according to a single item. Results: We analyzed 75, 358 questionnaires. The average age of participants was 73.8 ± 6.0 years, and 55.0% were women. An ordered logistic regression analysis showed that lower childhood socioeconomic status was associated with lower physical function, independent of adult sociodemographic factors, health behaviors, and health conditions. This association was stronger in women than in men. Conclusions: Our findings indicate that low childhood socioeconomic status might have a long-term influence on physical function in late life and that this influence varies by sex. Assessment of socioeconomic disadvantage in childhood is important for developing strategies to help older people maintain their physical function longer.